Investigation of groundwater quality in “Kiramakodu area” of Point Pedro: Vadamarachi aquifer, Northern Sri Lanka - Velauthamurty, K.; Praveena, R.; Raagulan, K. (University of Jaffna, 2020)
Water is one of the essential part for the existence of life on the earth crust. Over the past decades, demand for the potable water has significantly increased due to the deteriorating anthropogenic activity. Jaffna peninsula completely relies on the groundwater for all the purposes such as domestic, industrial and agriculture. The overpopulation destroyed the freshwater reservoirs and diminishes the natural potable source. This study focuses on a water quality parameters such as pH, turbidity, calcium, magnesium, chloride, sulphate, sodium, potassium, fat, oil and grease (FOG) in vaddamarachi aquifer and calcium (149.17-183.61 ppm), sodium (847.88-1222.99 ppm) and chloride (525.53- 924.80 ppm) content of most of the samples are higher than that of Sri Lankan standard for potable water. This study provides the basic information for the future medical study and gives awareness of water conservation in the region.
Keywords: Contamination; Fat; Oil and grease; Groundwater; Industrialization; Jaffna peninsula; Water quality parameters